The Sierra Madre Sports Rehabilitation Resort - Rasmussen, Klaudine Merl O. (College of Architecture, University of the Philippines Diliman, 2019)
The sports industry in the Philippines thrives in the local and global scenes. Special health services directed for sports are part of the sports infrastructure that promote holistic well-being. However, sports rehabilitation programs in the Philippines are primarily focused on the physical aspects of rehabilitation. Moreover, the environment of hospitals and rehabilitation centers further stresses the patients which adds to the stress they already experience from their sports injuries. The fear of losing body parts and/or functions, and the anxiety from not knowing the outcome of treatments contribute to their stress. (Chhari, 2016). This thesis seeks to aspect of mental health that directly affects patients in musculoskeletal rehabilitation, and their overall wellness and performance thereafter. As the current accepted trend of recovery involving such injuries includes both alternative and scientific practices, their co-existence in one project development is integrated. Alternative treatment practices were chosen in accordance to those that have already been approved and accepted by the scientific medical community as such practices are progressively proven to be effective despite concepts of psychosocial healing and stress-reducing environments. Hence, they are ultimately addressed through design translations in the architecturally-built environment of The Sierra Madre Sports Rehabilitation Resort, a short to long-term stay-in community resort at the foot of the Sierra Madre in Tanay, Rizal.